Gender impacts the post-exercise substrate and endocrine response in trained runners - Vislocky, L.; Gaine, P.; Pikosky, M.; Martin, W.; Rodriguez, N. (Journal of the International Society of Sports Nutrition, 2008)
Although several studies have investigated gender differences in the substrate and endocrine responses during and following endurance exercise, few have studied sex differences during a more prolonged recovery period post endurance exercise. The purpose of this study was to compare and characterize the endocrine and substrate profiles of trained male and female adult runners during the three-and-a-half hour recovery period from an endurance run.